The liverworts (Marchantiophyta) of the state of Goiás, Brazil - Gradstein, S. Robbert; Schäfer-Verwimp, Alfons; Costa, Denise Pinheiro da (Revista de Biologia Neotropical / Journal of Neotropical Biology, 2018)
Ver resumo em pdf no artigo.